The Impact of Testing on the Formation of Children's and Adults' False Memories. Issue 5 (19th July 2016) - Brackmann, Nathalie; Otgaar, Henry; Sauerland, Melanie; Howe, Mark L.
Summary: Witnesses are frequently questioned immediately following a crime. The effects of such testing on false recall are inconclusive: Testing may inoculate against subsequent misinformation or enhance false memory formation. We examined whether different types of processing can account for these discrepancies. Drawing from Fuzzy‐trace and Associative‐activation theories, immediate questions that trigger the processing of the global understanding of the event can heighten false memory rates. However, questions that trigger the processing of specific details can inoculate memories against subsequent misinformation. These effects were hypothesized to be more pronounced in children than in adults. Seven/eight‐, 11/12‐, 14/15‐year‐olds, and adults (N = 220) saw a mock‐theft film and were tested immediately with meaning or item‐specific questions. Test results on the succeeding day replicated classic misinformation and testing effects, although our processing hypothesis was not supported. Only adults who received meaning questions benefited from immediate testing and, across all ages, testing led to retrieval‐enhanced suggestibility. © 2016 The Authors. Applied Cognitive Psychology Published by John Wiley & Sons, Ltd.